Transcriptional networks orchestrating programmed cell death during plant development - Cubría-Radío, Marta; Nowack, Moritz K (Current topics in developmental biology, 2019)
Transcriptional gene regulation is a fundamental biological principle in the development of eukaryotes. It does control not only cell proliferation, specification, and differentiation, but also cell death processes as an integral feature of an organism's developmental program. As in animals, developmentally regulated cell death in plants occurs in numerous contexts and is of vital importance for plant vegetative and reproductive development. In comparison with the information available on the molecular regulation of programmed cell death (PCD) in animals, however, our knowledge on plant PCD still remains scarce. Here, we discuss the functions of different classes of transcription factors that have been implicated in the control of developmentally regulated cell death. Though doubtlessly representing but a first layer of PCD regulation, information on PCD-regulating transcription factors and their targets represents a promising strategy to understand the complex machinery that ensures the precise and failsafe execution of PCD processes in plant development.